Analysis of the Influence of Innovative Attitudes, Integrated Management Information Systems on Education Management Performance 4.0 in Mediation Employee Job Satisfaction at the University Development of Pancabudi Medan - Muhammad Isa Indrawan; Rahul Ardian Fikri; Elfitra Desy Surya (International Journal of Management, Economic and Accounting, 2024)
Pancabudi Development University Medan is one of the private universities that always prioritizes the quality of its Human Resources. The purpose of this study is to examine and analyze the effect of innovation attitudes, education management information systems on the performance of education management 4.0 mediated by job satisfaction at Pancabudi Development University Medan. This research study uses a quantitative approach that uses Structural Equation Modeling (SEM) analysis tools. The sample amounted to 100 employees. The research findings are that there is no effect of the education management information system on the performance of education management 4.0 at Pancabudi Development University Medan. Overall, this study shows that there is a positive and significant influence between innovative attitudes, integrated education management information systems on education management performance 4.0 mediated by job satisfaction at Pancabudi Development University Medan.